Role of black grandmothers in the racial socialization of their biracial grandchildren - Chancler, Lover LM (Kansas State University, 2014)
The current study was focused on the role Black grandmothers played in biraical (Black and White) racial socialization process of their grandchild or grandchildren. Racial socialization process where by the grandmothers engaged in a systemtic and deliberate attempt to ensure that their grandchildren develp an awareness and sensibilty toward their Black hertiage. There were several criteria the grandmothers had to meet. They included being born before 1975, ensuring that the grandmothers expereienced the post 70s Black pride movement. The grandmother also needed to have contact with the identified grandchild. Qualitative methods with a phenomenological lens were employed. The Black grandmothers are seen as the experts on their experiences, thus phenomenology allowed me to probe deeper into the experiences of these grandmothers and their reality. One-on-one interviews were conducted with the participants at the location and time of their choice. The results revealed the perspective and methods they exercised in racially socializing their biracial grandchildren. The participants had similar beliefs as it related to what their role in the racial socialization process was supposed to be. There were eight primary themes that emerged were community influence, spirituality, social adjustment, feelings toward “the other”, social perception, cultural indoctrination, grandma’s burden, and the road ahead. Although, each grandmother had a different journey their conclusions regarding the way to socialize their biracial grandchildren as Black was unanimous.
Keywords: Grandmothers; Biracial; Socialization; Race relations; Individual & Family Studies (0628)